Mucilage protects the planktonic desmid Staurodesmus sp. against parasite attack by a chytrid fungus - Van Den Wyngaert Silke; Kainz Martin J; Ptacnik Robert (OXFORD UNIV PRESS, 2025)
Zoosporic fungi of the phylum Chytridiomycota are ubiquitous parasites of phytoplankton in aquatic ecosystems, but little is known about phytoplankton defense strategies against parasitic chytrid attacks. Using a model chytrid-phytoplankton pathosystem, we experimentally tested the hypothesis that the mucilage envelope of a mucilage-forming desmid species provides protection against the parasitic chytrid Staurastromyces oculus. Mucilage-forming Staurodesmus cells were not accessible to the chytrid, whereas physical removal of the mucilage envelope rendered the same Staurodesmus sp. strain equally susceptible to chytrid infections as the original non-mucilage-forming host Staurastrum sp. Epidemic spread of the parasite only occurred in Staurastrum sp., whereas non-mucilage-bearing Staurodesmus sp. allowed for co-existence of host and parasite, and mucilage-bearing Staurodesmus sp. caused parasite extinction. In addition to the mucilage defense barrier, we also demonstrate the ability of both Staurastrum sp. and Staurodesmus sp. to resist infection by preventing chytrid development while still remaining viable and being able to reproduce and thus recover from an infection. This study extends our knowledge on phytoplankton defense traits and the functional role of mucilage in phytoplankton as a physical barrier against fungal parasites.